2009
DOI: 10.1007/s12325-009-0078-6
|View full text |Cite
|
Sign up to set email alerts
|

LigaSure versus clamp-and-tie in thyroidectomy: a single-center experience

Abstract: Purpose: LigaSure (ValleyLab, CO, USA) is a bipolar diathermy system that seals vessels with reduced thermal spread. The device has been used successfully in abdominal surgery and has been introduced as a new method for hemostasis during thyroidectomy. This study compares the efficacy and advantages of LigaSure, when used for thyroidectomy in benign nodular thyroid disease, with the conventional clamp-and-tie technique. Methods: Between December 2003 and December 2008, 410 patients underwent thyroid surgery (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…When it was soaked by 50 % the means that it contains about 25 ml of blood and if totally soaked; 100% this means that it contains 75 ml of blood [16]. Many researchers reported significant reduction of intra-operative blood loss by the use of ligasure system in total thyroidectomy when compared with the conventional sutureligation technique [6,17,18,19] and our data came in agreement with those reported results. The ligasure vessel sealing system can apply control, sealing vessels up to 7 mm in diameter and facilitates surgery by achieving the efficient haemostasis of blood vessels encountered during dissection, and allowing the rapid and secure division of vascularised tissues, while minimizing thermal injury to adjacent tissues [20].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…When it was soaked by 50 % the means that it contains about 25 ml of blood and if totally soaked; 100% this means that it contains 75 ml of blood [16]. Many researchers reported significant reduction of intra-operative blood loss by the use of ligasure system in total thyroidectomy when compared with the conventional sutureligation technique [6,17,18,19] and our data came in agreement with those reported results. The ligasure vessel sealing system can apply control, sealing vessels up to 7 mm in diameter and facilitates surgery by achieving the efficient haemostasis of blood vessels encountered during dissection, and allowing the rapid and secure division of vascularised tissues, while minimizing thermal injury to adjacent tissues [20].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the operative time, our data came in concordance with those reported in previous studied and the authors of these studies found significant difference in operative time reduction in case of ligasure [6,11,12,13]. The conventional suture knot tying technique requires a large number of surgical ties and this maneuver is time consuming and requires good exposure [7] Estimation of intra-operative blood loss is governed by visual method [14] and the clinical assessment with collaboration with the anesthetist [15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…There are several standard techniques for mastery of bleeding complications like suture ligation of individual vessels and electrocoagulation [7]. In addition to these standard techniques, the new haemostatic devices like Ligasure ® [19] and Harmonic Scalpel [20] (e.g.) which have proven to decrease the risk for postoperative bleeding and intra-operative blood loss [21], could be useful in the surgical management of postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%